2018
DOI: 10.1002/anie.201802397
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Formation of (E)‐β‐Vinylstannanes with a Topologically Controlled Molybdenum‐Based Alkyne Hydrostannation Catalyst

Abstract: The regioselective formation of (E)-β-vinylstannanes has been a long-standing challenge in transition-metal-catalyzed alkyne hydrostannation. Herein, we report a well-defined molybdenum-based system featuring two encumbering m-terphenyl isocyanides that reliably and efficiently delivers (E)-β-vinylstannanes from a range of terminal and internal alkynes with high regioselectivity. The system is particularly effective for aryl alkynes and can discriminate between alkyl chains of low steric hindrance in unsymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…But the example of the Re(III) complex also shows that the corresponding IR frequencies are sensitive to other structural features such as the trans ligand (here Cl – vs. PPh 3 ). Similar findings have been reported earlier for various complexes with m ‐terphenylisocyanides . Thus, the absolute values of these stretches should be regarded with suspicion in the discussion of the bonding situation in such compounds.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…But the example of the Re(III) complex also shows that the corresponding IR frequencies are sensitive to other structural features such as the trans ligand (here Cl – vs. PPh 3 ). Similar findings have been reported earlier for various complexes with m ‐terphenylisocyanides . Thus, the absolute values of these stretches should be regarded with suspicion in the discussion of the bonding situation in such compounds.…”
Section: Resultssupporting
confidence: 88%
“…This dual property allows isocyanides to bind well to transition metals in a range of formal oxidation states. It has been previously reported that m ‐terphenyl isocyanides can stabilize unusual low‐valent complexes of both manganese and molybdenum,, but also some medium to high valent m ‐terphenyl isocyanide complexes of Mn and Mo have been isolated via chemical oxidation of low‐valent precursors,, thereby demonstrating the utility of these encumbering ligands across a range of metal‐based redox states. Very recently, we studied reactions of m ‐terphenyl isocyanides with technetium complexes of various oxidation states and found that even technetium(V) complexes with these ligands are stabilized when strong donors such as nitrido or phenylimido ligands are present .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…14 This inspired the synthesis of other complexes containing cyclo-P 4 ligands a few of which were recently reported as e.g. being based on rare earth metals like [{(DippForm) 2 Sm} 2 (m,h 4 :h 4 -P 4 )], 15 group ve metals, [Cp R M(CO) 2 (h 4 -P 4 )] (M ¼ V, Nb, Ta (A)), 16 on chromium, [L 2 Cr 2 (h 2 :h 2 :h 1 :h 1 -P 4 )] (L ¼ (2,6-diisopropylphenyl)-{6-(2,6dimethylphenyl)-pyridin-2-yl}-amide)), 17 on iron, [ Ph PP 2 Cy Fe(h 4 -P 4 )] (B), 18 on molybdenum, [(Ar Dipp CN) 2 Mo(CO) 2 (h 4 -P 4 )] (C) 19 and on the anionic iron complex [Cp Ar Fe(h 4 -P 4 )] À (ref. 20) as well as on the anionic cobalt complex [(PHDI)Co(h 4 -P 4 )] À (D).…”
Section: Introductionmentioning
confidence: 99%
“…)), which serves as a reactive source of the 14efragment [Mo(CO)2(CNAr Dipp2 )2] by virtue of facile displacement of its  2 -C,H: 1 -N-diisopropylamine chelate. [20] and 5 (bottom). [40] Treatment of 1 with 1.0 equiv of white phosphorus in an npentane/toluene mixture proceeds in near-quantitative yield with the exclusive formation of a single diamagnetic product, as assayed by 1 H and 31 P NMR spectroscopy.…”
mentioning
confidence: 99%